2019
DOI: 10.1111/gwao.12383
|View full text |Cite
|
Sign up to set email alerts
|

New masculinities in universities? Discourses, ambivalence and potential change

Abstract: In this article, we explore forms and possible implications of new masculinities in universities, and elucidate how they relate to hegemonic masculinity. ‘New masculinities’ coins a particular tradition of naming in Nordic masculinity studies. In the Nordic context, gendered social relations are shaped by State policies and equality discourses, which are increasingly embracing father‐friendly initiatives. New masculinities refers to the increased involvement of men in caring practices and especially in fatheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 63 publications
(119 reference statements)
0
35
0
Order By: Relevance
“…However, greater involvement in care work at home has not necessarily carried over into the workplace. Lund, Meriläinen and Tienari (2019) concluded that 'the idea of choice serves to uphold a more traditional masculinity -and its statuseven when heteronormative distinctions between the masculine and the feminine are sometimes downplayed in portrayals of everyday family life' (p. 1390). Ladge et al (2015) note that 'expectations of fathering have dramatically changed over time ' (p. 154), however, 'while many fathers aspire to be more involved in caregiving, gendered and workplace norms can still inhibit them from fully doing so' (p. 165).…”
Section: Management and Masculinitymentioning
confidence: 99%
“…However, greater involvement in care work at home has not necessarily carried over into the workplace. Lund, Meriläinen and Tienari (2019) concluded that 'the idea of choice serves to uphold a more traditional masculinity -and its statuseven when heteronormative distinctions between the masculine and the feminine are sometimes downplayed in portrayals of everyday family life' (p. 1390). Ladge et al (2015) note that 'expectations of fathering have dramatically changed over time ' (p. 154), however, 'while many fathers aspire to be more involved in caregiving, gendered and workplace norms can still inhibit them from fully doing so' (p. 165).…”
Section: Management and Masculinitymentioning
confidence: 99%
“…LeFeuvre et al examine different forms of R&I labour markets in relation to early career arrangements and gender equality in six European countries, not including Finland, Norway, or Sweden, the countries we focus on in this article. Although gender inequalities in R&I occur in all six countries and manifest similar gendered subtle discriminatory patterns, for example in recruitment (Herschberg et al, 2019) and in combining family and work in 'greedy' R&I institutions (Krilic et al, 2019), they argue that it is the local institutional contexts that primarily matter in issues of gender inequality in R&I (see also Gatrell, 2011;Lund et al, 2019;Pecis, 2016). Our study thus contributes to knowledge about gender and R&I careers by focusing on the institutional contexts prevailing in the Nordic countries.…”
mentioning
confidence: 74%
“…Although this does not make parenting gender equal, it could potentially have significant effects on women's opportunities in R&I work, at least in the early career stages, if R&I institutions themselves did not exercise informal discriminatory practices (cf. Lund et al, 2019;Thun, 2020). Childcare provision as such was not regarded as discriminatory, but R&I institutions' decisions to move projects and research centres to other researchers, usually men, when women were on parental leave, for example, was.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, I asked those men academics in the field whose scholarly works are palpably inflected by the principles of gender inclusivity and equity. Whether or not they have engaged with feminist theorizing (Prasad, 2012; Pullen & Rhodes, 2014) or specifically considered the position of men and masculinity within feminist movements (Lund, Merilainen, & Tienari, 2019; Tienari & Taylor, 2019), their work, broadly speaking, has encapsulated the spirit of gender inclusivity and equity (e.g., Alamgir & Alakavuklar, 2020; Nisar, 2018). The second issue related to the practice of inclusivity and equity.…”
Section: Ajnesh Prasadmentioning
confidence: 99%